Elections, protest and trust in government: A natural experiment from Russia - Timothy Frye; Ekaterina Borisova (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
How do flawed elections and post-election protest shape political attitudes? Taking advantage of the largely exogenous variation in the timing of a survey conducted in Moscow, we examine the short-term impact of the parliamentary election of December 4th, and the large protest of December 10th on trust in the Russian government. The fraud-marred parliamentary election had little effect on attitudes toward government, perhaps because allegations of vote improprieties were not new information. In contrast, the large protest of December 10th increased trust in government. Heightened trust arises largely from non-supporters of the ruling party updating their beliefs rather than from social desirability bias, a perceived improvement in government performance, or a "halo" effect. This finding is consistent with the view that autocrats can increase trust in government by unexpectedly allowing protest without repression. It also suggests that when evaluating trust in government citizens may cue not off the content of the protest, but off the holding of the protest itself.
URN:NBN:fi:bof-201608221384
Keywords: P26; D72; 330